EVALUATION OF MODIFIED ALVARADO SCORE FOR FREQUENCY OF NEGATIVE APPENDICECTOMIES - Kamran, Haider; Naveed, Danish; Asad, Shawana; Hameed, Muhammad; Khan, Umar (Journal of Ayub Medical College Abbottabad, 2010)
Background: Appendicitis being the commonest surgical emergency is primarily diagnosed clinically but posses diagnostic difficulty usually, especially to junior surgeons, demanding the need for tool/scoring system that can be easily applicable, accurate & reproducible in the diagnosis of appendicitis, with low negative Appendicectomy rate. This study is designed to assess one such scoring system, i.e., Modified Alvarado Score. Methods: A total of 100 consecutive male and female patients with age 10 year and above presenting with symptoms suggestive of acute appendicitis were included in study, assessed according to eight variables of Modified Alvarado scoring system and were accordingly placed into 3 groups. Group-I patients having score 1-4 were discharged, Group-II patients having score 5-7 were observed while Group-III patients having score 8-10 were operated. Status of appendix of operated patients was assessed histo-pathologically. Results: Out of 100 patients included in study, 58 patients were operated on the basis of said scoring system. Of the operated patients 52 (89.65%) had acute appendicitis, thus yielding a positive predictive value of 89.66% while negative appendectomy rate of 10.34%. Frequency of negative appendicectomy was 7.69% (3/39) amongst males and 15.79% (3/19) in females. Post-operative complication rate including wound infection, pelvic abscess, chest and urinary tract infection was 22.41% (13/58). Conclusion: Frequency of the negative appendicectomies can be reduced through standardization of the diagnostic procedure, by applying Modified Alvarado score in the diagnosis of suspected appendicitis cases as compared to simple clinical assessment. Keywords: Appendicitis, Modified Alvarado Score, frequency, appendicectomy